The Strategy for Preventing Police Misconduct through a Human-Centered Policing Approach - bachtiar; Imanuddin, Iman; Aringga, Rino Dedi; Saputra, Agung Arafat; Rifkhan (Jurnal Ilmu Kepolisian, 2026)
Public trust constitutes the primary foundation of the legitimacy of police institutions in democratic states. In Indonesia, a series of cases involving personal misconduct by members of the Indonesian National Police (Polri) throughout 2025, including serious criminal offenses and incidents that generated negative public opinion, indicate that institutional delegitimization is more frequently driven by the behavior of law enforcement personnel than by weaknesses in formal regulatory frameworks. This article aims to analyze the impact of personal misconduct on the legitimacy of the Polri institution and to propose a human-centered policing approach as a strategy for preventing misconduct and restoring legitimacy. The research employs a normative juridical method with conceptual and sociological approaches. Data were collected through a targeted review of statutory regulations, academic literature, and police policy documents, particularly internal oversight and public complaint data, and were evaluated using thematic analysis. Consequently, the conceptual and policy analysis indicates that police legitimacy depends not only on formal legal authority but, more importantly, on moral integrity, ethical compliance, and public trust. The human-centered policing approach positions police personnel as human subjects with psychological, social, and moral complexities, thereby emphasizing personnel development, early detection mechanisms, and welfare support as proactive strategies to prevent personal misconduct. When implemented consistently, this approach not only strengthens internal legitimacy and institutional integrity but also builds a sustainable foundation of public trust, ultimately fostering a police institution that is professional, accountable, and democratic.